2010
DOI: 10.1021/bi100128h
|View full text |Cite
|
Sign up to set email alerts
|

Myelin Basic Protein and Myelin Protein 2 Act Synergistically to Cause Stacking of Lipid Bilayers

Abstract: Saltatory conduction of nerve impulses along axonal membranes depends on the presence of a multilayered membrane, myelin, that wraps around the axon. Myelin basic protein (MBP) and myelin protein 2 (P2) are intimately involved in the generation of the myelin sheath. They are also implicated in a number of neurological diseases, including autoimmune diseases of both the central and peripheral nervous systems. Here, we have used atomic force microsopy (AFM) to study the effects of MBP and P2 on lipid bilayers. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 45 publications
(74 reference statements)
3
71
0
Order By: Relevance
“…Recent biochemical data suggested that Mbp might interact with Pmp2 to form and maintain compact myelin (Suresh et al, 2010). Interestingly, shiverer mice (carriers of an autosomal recessive mutation for Mbp) possess severe myelin defects in the CNS, but not in the PNS (Dupouey et al, 1979;Mikoshiba et al, 1981).…”
Section: In Vivo Analysis Of Potential Pmp2-mbp Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent biochemical data suggested that Mbp might interact with Pmp2 to form and maintain compact myelin (Suresh et al, 2010). Interestingly, shiverer mice (carriers of an autosomal recessive mutation for Mbp) possess severe myelin defects in the CNS, but not in the PNS (Dupouey et al, 1979;Mikoshiba et al, 1981).…”
Section: In Vivo Analysis Of Potential Pmp2-mbp Interactionmentioning
confidence: 99%
“…6c and a detailed list of lipid species contributing more than 0.5% to the total mass spectrometry signal is provided in Supporting Information Table S1. Pmp2 is known to bind fatty acids (Maddalo et al, 2010;Sedzik and Jastrzebski, 2011;Uyemura et al, 1984) and to interact with membrane bilayers (Ruskamo et al, 2014;Suresh et al, 2010). We therefore further explored the role of Pmp2 in lipid transport to or from membrane vesicles by using the fluorescent fatty acid analog DAUDA.…”
Section: Figurementioning
confidence: 99%
“…P2 is known to stack lipid bilayers together [7,11] and stabilize the membrane structure [12]. Previous neutron scattering studies have shown that P2 bound to myelinmimicking vesicles made either of 1,2-dimyristoyl-snglycero-3-phosphatidic acid (DMPA) or of a binary mixture of 1,2-dioleoyl-sn-glycero-3-phospho-L-serine (DOPS) and 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC), respectively, reduces the lipid dynamics [13].…”
Section: Introductionmentioning
confidence: 99%
“…MBP-C1 and MBP-C8 were prepared as described elsewhere [13]. For membrane samples, large multilamellar vesicles (ULVs) of DOPS:DOPC lipids were prepared by dissolving the lipids in chloroform (in a 1:1 mass ratio).…”
Section: Methodsmentioning
confidence: 99%